On Bicomplex Jacobsthal Numbers - Kilic, Nayil (Communications in Mathematics and Applications, 2021)
In this article, bicomplex Jacobsthal and bicomplex Jacobsthal-Lucas numbers are introduced and some properties related to them are investigated.